Polyvictimization Among Russian Sex Workers: Intimate Partner, Police, and Pimp Violence Cluster With Client Violence - Peitzmeier, Sarah M. (Journal of interpersonal violence, 2021)
Female sex workers (FSW) are a key population in the HIV epidemic and face high levels of violence. While women globally are predominantly at risk of intimate partner violence (IPV), FSW are additionally vulnerable to violence from clients, police, and pimps associated with their occupation. FSW are therefore at risk of cumulative trauma from polyvictimization, or violence from multiple types of perpetrators. Polyvictimization is a driver of morbidity and mortality in numerous populations, but there has been little research on how multiple types of victimization are related to one another in FSW. A cross-sectional survey was conducted among 754 FSW from three cities in the Russian Federation. Surveys assessed lifetime experiences of client, police, intimate partner, and pimp violence. Multivariate log-binomial and Poisson regression were used to test associations between these types of violence. Forty-five percent experienced any type of violence, including 31.7% from clients, 16.0% from police, 15.7% from intimate partners, and 11.4% from pimps. One fifth (20.4%) experienced polyvictimization. Client violence was central to polyvictimization: Only 5.9% of polyvictimization occurs without client violence. When client violence was not present, police, pimp, or IPV co-occurred significantly less than would be expected under an assumption that these types of violence occur independently (p < .001). However, they co-occurred more than would be expected when client violence is present. After adjusting for other types of violence experienced and demographic factors, experiencing client violence was independently associated with police violence (adjusted relative risk [ARR] = 2.77, 95% confidence interval [CI] [1.67, 4.59]), IPV (ARR = 3.67, 95% CI [1.95, 6.89]), and pimp violence (ARR = 5.26, 95% CI [2.80, 9.86]). Client violence may drive exposure to other types of violence and enable polyvictimization in a way that other types of violence do not in this setting. Violence prevention interventions may achieve maximal effect in reducing multiple types of violence by focusing on client violence.